2005
DOI: 10.1080/08860220500242967
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Duplex Ultrasound-Guided Manual Declotting and Percutaneous Transluminal Angioplasty in Thrombosed Native Dialysis Fistulas

Abstract: Background. To investigate the safety, feasibility, efficacy, and long-term patency rate of manual declotting under duplex ultrasound (US) guidance followed by percutaneous transluminal angioplasty (PTA) in thrombosed native arteriovenous fistulas (AVFs). Methods. Of 87 consecutive thrombosed AVFs evaluated by duplex US, 22 patients with 25 recently thrombotic events in 22 AVFs were suitable for manual declotting. PTA was performed following successful declotting, and long-term patency was assessed. Results. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…The degree of residual stenosis after angioplasty can be measured with ultrasound [13]. Bacchnini et al [14] found that after successful angioplasty of venous stenoses, access blood flow measured by ultrasound increased dramatically and returned to baseline flow values obtained before a stenosis had developed.…”
Section: Shenoy and Darcymentioning
confidence: 98%
“…The degree of residual stenosis after angioplasty can be measured with ultrasound [13]. Bacchnini et al [14] found that after successful angioplasty of venous stenoses, access blood flow measured by ultrasound increased dramatically and returned to baseline flow values obtained before a stenosis had developed.…”
Section: Shenoy and Darcymentioning
confidence: 98%
“…In particular we had access to all radiological procedures and we were able to characterize the exact location and the intervention performed in all dysfunctional AV accesses. AV access thrombosis treatment success can range from 88 to 100%, with post-intervention primary patency rates ranging from 9% to 49% at 1 year [22][23][24] . In our study, primary patency following treatment of thrombosis was 49% (22-71) at 1 year, however the difference between primary-assisted and secondary patency was only 2%.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate significant recoil of the stenosis should be further addressed by prolonged balloon angioplasty, cutting balloon, stenting, or even direct surgical revision so as to ensure a durable result of the procedure. Some adjuvant maneuvers such as manual declotting without or with ultrasound guidance, 13 suction thrombectomy through a mini-venotomy, or irrigation with lytic solution (250 KU urokinase in 10 ml of normal saline) may sometimes be helpful in difficult procedures.…”
Section: Endovascular Salvage For Thrombosis Of Arteriovenous Fistulamentioning
confidence: 99%